Remodelling of corticostriatal axonal boutons during motor learning - Mengjun Sheng; Di Lu; Richard H. Roth; Fuu-Jiun Hwang; Kaiwen Sheng; Jun B. Ding (Nature, 2025)
Abstract Motor skill learning induces long-lasting synaptic plasticity at dendritic spines1–4 and at the outputs of motor cortical neurons to the striatum5,6. However, little is known about corticostriatal axon activity and structural plasticity during learning in the adult brain. Here, using longitudinal in vivo two-photon imaging, we tracked thousands of corticostriatal axonal boutons in the dorsolateral striatum of awake mice. We found that learning a new motor skill dynamically regulated these boutons. The activities of motor corticostriatal axonal boutons exhibited selectivity for rewarded movements (RM) and unrewarded movements (UM). Notably, boutons on the same axonal branches showed diverse responses during behaviour. Motor learning significantly increased the proportion of RM boutons and reduced the heterogeneity of bouton activities. Moreover, motor learning induced profound structural dynamism in boutons. By combining structural and functional imaging, we saw that newly formed axonal boutons were more likely to exhibit selectivity for RM and were stabilized during motor learning, whereas UM boutons were selectively eliminated. These findings reveal a novel form of plasticity in corticostriatal axons and show that motor learning drives dynamic bouton reorganization to support motor skill acquisition and execution.